Core loss measurements of three phase AC induction motor - Ismail, Daut, Prof. Dr.; Anayet, Karim; Gomesh Nair, Shasidharan; Asri, N.; Syatirah; Muzhar, M. (Institute of Electrical and Electronics Engineers (IEEE), 2011)
Link to publisher's homepage http://ieeexplore.ieee.org/